IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK DENGAN VIDEO ANIMASI DALAM MENINGKATKAN TANGGUNG JAWAB BELAJAR SISWA SAAT PANDEMI DI SMA WACHID HASYIM 5 SURABAYA - Nur Khayati; Maghfirotul Lathifah; Sutijono Sutijono (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2022)
This study was followed by a pandemic phenomenon in which learning was boldly carried out. Bold learning has an impact on students’ declining learning responsibilities. Learning responsibility is the obligation to completely completely completely accomplish tasks through utmost effort and courageously bear all the consequences. This study constitutes a type of quantitative research by using the pre-experimental one-group pre-test post-test design method. The samples that this study used were purposive sampling with criteria students late in task collection, students late in taking learning, students never collected tasks. The data analysis technique used is a nonparametric statistical analysis using Wilcoxon tests. Research results that the implementation of group guidance services with animated videos is effective in enhancing students’ learning responsibility.